A Proposal that the Coal Industry be let Alone - Gandy, Harry L. (Quarterly Journal of Economics, 1925)
Journal Article A Proposal that the Coal Industry be Let Alone Get access Harry L. Gandy Harry L. Gandy National Coal Association, Washington Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 39, Issue 3, May 1925, Pages 484–488, https://doi.org/10.2307/1882441 Published: 01 May 1925